Reliability and validity of a Dutch Lymphoedema Questionnaire: Cross‐cultural validation of the Norman Questionnaire. (15th May 2020) - De Groef, An; De Vrieze, Tessa; Dams, Lore; Penen, Frauke; Van der Gucht, Elien; Van Assche, Brecht; Verhaeghe, Vincent; Devoogdt, Nele
Abstract: Objective: To perform the cross‐cultural validation process of the Dutch Norman Questionnaire (NQ), a questionnaire for the detection and characterisation of breast‐cancer related lymphoedema (BCRL) using self‐reported signs and symptoms. Methods: Test‐retest reliability and construct (including convergent, divergent and known‐groups validity), face and content validity were examined in breast cancer patients with ( n  = 30) and without ( n  = 30) lymphoedema. For concurrent validity, first, agreement between the diagnostic item of the NQ and a clinical diagnosis were analysed. Second, correlations between NQ scores and clinical arm volume assessment were tested. Results: Test‐retest reliability was found to be strong to very strong (ICC 0.79–0.96) in the lymphoedema group and moderate to very strong ( ICC 0.64–0.99) in the non‐lymphoedema group. Seventeen out of 20 hypotheses on convergent and divergent validity were accepted. There was good face, content and known‐groups validity as well. For concurrent validity, agreement between evaluation methods was only 0.462. Moderate correlations were found between 6 out of 9 symptom scores (r = 0.422–0.630) of the NQ and clinical assessment. Conclusion: The Dutch NQ is a reliable and valid questionnaire for the characterisation of BCRL using self‐reported signs and symptoms. Only moderate agreement for the detection of BCRL was found.